The coexistence in an educational center: organizational keys for its empowerment - Ramos Corpas, Manuel Jesús (Avances en Supervisión Educativa, 2010)
The article consists of two different parts. The first part is a theoretical analysis of violence prevention strategies, primary, secondary and tertiary levels aimed at improving coexistence. And, in the second part, the analysis of practice in the center during the academic years from 2004/2005 to 2008/2009 is integrated. Finally results are presented.